Host resistance to pulmonary Mycobacterium tuberculosis infection requires CD153 expression. (November 2018) - Sallin, Michelle; Kauffman, Keith; Riou, Catherine; Bruyn, Elsa; Foreman, Taylor; Sakai, Shunsuke; Hoft, Stella; Myers, Timothy; Gardina, Paul; Sher, Alan; Moore, Rashida; Wilder-Kofie, Temeri; et al.
Abstract Mycobacterium tuberculosis infection (Mtb) is the leading cause of death due to a single infectious agent and is among the top ten causes of all human deaths worldwide1 . CD4 T cells are essential for resistance to Mtb infection, and for decades it has been thought that IFNγ production is the primary mechanism of CD4 T-cell-mediated protection2, 3 . However, IFNγ responses do not correlate with host protection, and several reports demonstrate that additional anti-tuberculosis CD4 T-cell effector functions remain unaccounted for4–8 . Here we show that the tumour-necrosis factor (TNF) superfamily molecule CD153 (encoded by the geneTnfsf8 ) is required for control of pulmonary Mtb infection by CD4 T cells. In Mtb-infected mice, CD153 expression is highest on Mtb-specific T helper 1 (TH 1) cells in the lung tissue parenchyma, but its induction does not require TH 1 cell polarization. CD153-deficient mice develop high pulmonary bacterial loads and succumb early to Mtb infection. Reconstitution of T-cell-deficient hosts with eitherTnfsf8 −/− orIfng −/ − CD4 T cells alone fails to rescue mice from early mortality, but reconstitution with a mixture ofTnfsf8 −/− andIfng −/− CD4 T cells provides similar protection as wild-type T cells. In Mtb-infected non-human primates, CD153 expression is much higher on Ag-specific CD4 T cells in the airways compared to blood, and the frequency of Mtb-specific CD153-expressing CD4 T cells inversely correlates with bacterial loads in granulomas. In Mtb-infected humans, CD153 defines a subset of highly polyfunctional Mtb-specific CD4 T cells that are much more abundant in individuals with controlled latent Mtb infection compared to those with active tuberculosis. In all three species, Mtb-specific CD8 T cells did not upregulate CD153 following peptide stimulation. Thus, CD153 is a major immune mediator of host protection against pulmonary Mtb infection and CD4 T cells are one important source of this molecule. CD153 expression by CD4 T cells is required for control of pulmonaryMycobacterium tuberculosis infection.